Association between regional body fat and cardiovascular disease risk among postmenopausal women with normal body mass index. (30th June 2019) - Chen, Guo-Chong; Arthur, Rhonda; Iyengar, Neil M; Kamensky, Victor; Xue, Xiaonan; Wassertheil-Smoller, Sylvia; Allison, Matthew A; Shadyab, Aladdin H; Wild, Robert A; Sun, Yangbo; Banack, Hailey R; Chai, Jin Choul; et al.
Abstract: Aims: Central adiposity is associated with increased cardiovascular disease (CVD) risk, even among people with normal body mass index (BMI). We tested the hypothesis that regional body fat deposits (trunk or leg fat) are associated with altered risk of CVD among postmenopausal women with normal BMI. Methods and results: We included 2683 postmenopausal women with normal BMI (18.5 to <25 kg/m 2 ) who participated in the Women's Health Initiative and had no known CVD at baseline. Body composition was determined by dual energy X-ray absorptiometry. Incident CVD events including coronary heart disease and stroke were ascertained through February 2017. During a median 17.9 years of follow-up, 291 incident CVD cases occurred. After adjustment for demographic, lifestyle, and clinical risk factors, neither whole-body fat mass nor fat percentage was associated with CVD risk. Higher percent trunk fat was associated with increased risk of CVD [highest vs. lowest quartile hazard ratio (HR) = 1.91, 95% confidence interval (CI) 1.33–2.74; P -trend <0.001], whereas higher percent leg fat was associated with decreased risk of CVD (highest vs. lowest quartile HR = 0.62, 95% CI 0.43–0.89; P -trend = 0.008). The association for trunk fat was attenuated yet remained significant after further adjustment for waist circumference or waist-to-hip ratio. Higher percent trunk fat combined with lower percent leg fat was associated with particularly high risk of CVD (HR comparing extreme groups = 3.33, 95% CI 1.46–7.62). Conclusion: Among postmenopausal women with normal BMI, both elevated trunk fat and reduced leg fat are associated with increased risk of CVD.